Peran dan Kedudukan Mediasi di Pengadilan Agama - Hermanto, Agus; Hidayat, Iman Nur; Hadaiyatullah, Syeh Sarip (Universitas Islam Negeri Raden Intan Lampung, 2021)
Mediation is a Religious Court facility in the context of resolving disputes outside the court, however, it is often found that the phenomenon of cases that have not been completed from the handling of mediation is often found. What is interesting to study is, what is the role and position of mediation in the religious courts? This paper aims to describe and analyze the role and position of mediation in the religious court environment, with this type of qualitative research in the form of library research, this study aims to examine in depth matters relating to the role and position of mediation in the religious courts environment. The conclusion in this study is that the mediation process has so far been carried out by the court with the position of the judge as a mediator, while the judge is the main role as well as the policy maker, so it becomes a very difficult task to be able to resolve cases outside the court, plus that a case that has been entered in to in court are cases that have been screened through family, community and even customary approaches, and have not been thoroughly visited which then refer to court.